2013
DOI: 10.1098/rspb.2012.2243
|View full text |Cite
|
Sign up to set email alerts
|

When ecosystem services interact: crop pollination benefits depend on the level of pest control

Abstract: Pollination is a key ecosystem service which most often has been studied in isolation although effects of pollination on seed set might depend on, and interact with, other services important for crop production. We tested three competing hypotheses on how insect pollination and pest control might jointly affect seed set: independent, compensatory or synergistic effects. For this, we performed a cage experiment with two levels of insect pollination and simulated pest control in red clover (Trifolium pratense L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 35 publications
7
110
0
Order By: Relevance
“…In addition, a well nutrient-balanced soil tends to reinforce plant health, hence their ability to resist pests (Altieri and Nicholls, 2003). Lundin et al (2013) observed a positive relationship between pollination and pest control resulting in an increased yield. These examples of synergies should encourage the implementation of multifunctional landscapes in an agroecological perspective (Fig.…”
Section: Enhancing Synergiesmentioning
confidence: 99%
“…In addition, a well nutrient-balanced soil tends to reinforce plant health, hence their ability to resist pests (Altieri and Nicholls, 2003). Lundin et al (2013) observed a positive relationship between pollination and pest control resulting in an increased yield. These examples of synergies should encourage the implementation of multifunctional landscapes in an agroecological perspective (Fig.…”
Section: Enhancing Synergiesmentioning
confidence: 99%
“…Currently, there is only one paper within the literature that focuses on this three way interaction and its impact on yield -the interaction of three species; bumblebees, Apion weevils and parasitic wasps, conducted in in laboratory conditions (Lundin et al, 2013). However, we have been unable to find a study that has investigated the interaction between pests, pollinators and pest-control in the field, nor linked such interactions to crop yields.…”
Section: Introductionmentioning
confidence: 74%
“…Whilst the interaction between pests and pestcontrol and has been studied (Chaplin-Kramer et al, 2011), the interaction between pests, pollinators and pest-control needs to be evaluated to establish the overall impact of ecosystem services provided by wildlife on agricultural systems, (Lundin et al, 2013). Currently, there is only one paper within the literature that focuses on this three way interaction and its impact on yield -the interaction of three species; bumblebees, Apion weevils and parasitic wasps, conducted in in laboratory conditions (Lundin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Undisturbed landscapes would increase the likelihood of solitary bee pollinator services in agricultural landscape (Morandin et al, 2007) which acts as a proxy for increasing wild pollinator densities (Melathopoulus et al, 2015). A recent study has demonstrated, for instance, that the benefit to crop yield from animal-mediated pollination depends on pest control levels (Lundin et al, 2013). However, pollinator-mediated yield is strongly conditioned by cultivar and their spatial arrangements in fields (Bellet al, 2012;Klatt et al, 2014), as well as environmental conditions and farm management practices (Boreux et al, 2013;Groeneveld et al, 2010;Hoover et al, 2012;Lundin et al, 2013;Melathopoulos et al, 2014).…”
Section: Discusssionmentioning
confidence: 99%